Food Allergy Investigations And Its Significance In Autism Spectrum Disorders - ANANTH N RAO; MINAKSHI KOCH; SABYASACHI GHOSH; SURESH KUMAR.V (International Journal of Pharma and Bio Sciences, 2010)
Autism is a developmental disorder with sensitivity to dietary and environmental antigens. Children with typical forms of autism to attention deficits frequently have sensitivities to certain foods. A food allergy is an IgE or IgG mediated reaction which shows symptoms within hours of having ingested the food. In the Department of Metabolic Diseases and Research, Apollo Hospital, serum samples of children, clinically diagnosed with Autism Spectrum Disorders (ASD) using DSM IV criteria, were tested for food allergy (IgE) on commonly used foods / food stuffs in a typical Indian cooking or form a part of the diet. We, in this study have attempted to demonstrate that the immediate or IgE mediated food allergy pattern is easily recognizable and anti-gliadin IgG in ASD studies is valuable. Improvement is seen with foods free from allergens recognized on the IgG/ IgE based investigation leading to speculation about a high prevalence of food allergy in ASD children.